Eugenol nanoemulsion reduces Listeria monocytogenes biofilm by modulating motility, quorum sensing, and biofilm architecture - Balasubramanian, Brindhalakshmi; Xue, Jingyi; Luo, Yangchao; Upadhyay, Abhinav (Frontiers in Sustainable Food Systems, 2023)
Listeria monocytogenes is a major foodborne pathogen in the United States that is capable of forming sanitizer-tolerant biofilms on diverse food contact surfaces and under varying temperature conditions. A plethora of research in the last decade has explored the potential of phytochemicals as antibiofilm agents. However, the low solubility of phytochemicals is a significant challenge that needs to be addressed to develop plant-based disinfectants that can be applied in the industry for controlling L. monocytogenes biofilms and improving food safety. This study investigated the efficacy of eugenol nanoemulsion (EGNE) in inhibiting biofilm formation in two strains of L. monocytogenes (Scott A and AT19115) on stainless steel surfaces at two temperatures (25 or 10°C). In addition, the effect of EGNE on pathogen motility, extracellular polymeric substances (EPS) production, eDNA production, and quorum sensing activity during biofilm formation was studied using standard bioassays. Moreover, the efficacy of EGNE in killing mature L. monocytogenes biofilm was also investigated against both the strains and temperature combinations. All experiments had a completely randomized design with duplicate samples and were repeated at least three times. EGNE had a particle size of 75 nm, a polydispersity index of 0.25, and a high negative surface charge. EGNE 700 mg/L inhibited L. monocytogenes biofilm formation significantly by 1.89 log in 72 h at 25°C and 1.25 log on day 16 at 10°C, when compared to control (p < 0.05). EGNE at 2,750 mg/L concentration completely inactivated ( 7 log CFU/coupon reduction as compared to control) L. monocytogenes biofilm cells developed at 25 or 10°C as early as 1 min of treatment time (p < 0.05). In addition, EGNE was able to significantly reduce the motility, EPS, eDNA production, and quorum sensing activity which plays a major role in biofilm formation. Both L. monocytogenes Scott A and AT19115 strains exhibited similar sensitivity to EGNE treatments. The results suggest that EGNE could potentially be used as a natural sanitizer to effectively control L. monocytogenes biofilms in food processing environments.